Impact of sleep quality on functional capacity, peripheral muscle strength and quality of life in patients with chronic obstructive pulmonary disease. (April 2015) - Vardar-Yagli, Naciye; Saglam, Melda; Savci, Sema; Inal-Ince, Deniz; Calik-Kutukcu, Ebru; Arikan, Hulya; Coplu, Lutfi
<x xml:space="preserve">Abstract</x> Purpose: The purpose of this study was to assess the impact of quality of sleep on functional capacity, peripheral muscle strength and quality of life in patients with chronic obstructive pulmonary disease (COPD). Materials and Methods: Forty patients with COPD (61.6 ± 8.28 years) were included in this study. Subjective sleep quality (Pittsburgh sleep quality index), quality of life (Nottingham health profile), quadriceps muscle strength (QMS) and functional capacity (6-min walk test) were assessed. Results: Poor sleep quality (Pittsburgh sleep quality index total >5) was present in 57% of the patients. Patients with a poor sleep quality had significantly lower QMS and higher exercise heart rate (p < 0.05). The Pittsburgh sleep quality index total score was associated with QMS, Nottingham health profile physical mobility and sleep scores, exercise fatigue and dyspnea (p < 0.05). Conclusion: Sleep quality is affected in a majority of patients with COPD. It is related with symptoms, functional capacity, peripheral muscle strength and general quality of life.